Index design and safety evaluation of pesticides application based on a fuzzy AHP model for beverage crops: tea as a case study. Issue 2 (21st August 2019) - Chen, Zongmao; Zhou, Li; Yang, Mei; Luo, Fengjian; Lou, Zhengyun; Zhang, Xinzhong; Sun, Hezhi; Wang, Xinru
Abstracts: BACKGROUND: A fuzzy analytic hierarchy process (AHP) is shown to be an effective methodology for multiple criteria decision‐making from various heterogeneous data. Despite application of AHP to some decision‐making problems in agriculture, research on AHP utilization for screening the safe use of pesticides for tea plantations based upon multiple criteria has not been reported. The overall safety chain from tea plantation to tea manufacture to tea cup after pesticides had been sprayed on a tea plantation was considered and the AHP network was constructed at two levels with two categories, tea‐related parameters and pesticide toxicity. Seven criteria were selected as safety indexes, half‐lives of pesticides on the tea plant (T1/2 ), water solubility (Ws), vapor pressure (Vp), acceptable daily intake (ADI), acute oral lethal dose of pesticides to rat (LD50 ), and ecotoxicity of pesticides including LD50 to bees and LD50 to aquatic organisms. RESULTS: According to the AHP, water solubility was the most important factor in the evaluation pesticide safety for use on a tea plantation, followed by the half‐lives of the pesticides on the tea plant and the acceptable daily intake. Combined with the scale of seven criteria and relative weight ( W ), 48 pesticides with an overall score ( S ) < 25 could be regarded as relatively safe compounds when applied in tea plantations. CONCLUSION: An AHP approach was suggested to evaluate the safe use of pesticides on tea plantations. This study provides a new idea for the evaluation of safety in beverage crops. © 2019 Society of Chemical Industry Abstract : There is a pressing need for methods guiding the scientific use of tea garden pesticides. The article presents the first application of a fuzzy AHP model of pesticide safety on a tea crop.